Enhanced Army Airborne Forces - Gordon, John IV; Schaefer, Agnes Gereben; Shlapak, David A.; Baxter, Caroline; Boston, Scott (RAND Corporation, 2023)
A RAND research team examined options to increase the mobility, protection, and firepower of Army airborne forces, given likely future missions and threats, and identified a concept for enhancing today’s forces by adding a light armored infantry capability. This report examines the numbers and types of vehicles that would be needed to create an airborne light armored force that could be airdropped or air-landed from Air Force transport planes.